The Fundamentals of Corporate Communication - Dolphin R. Richard (Butterworth Heinemann, 2000)
A contemporary examination of the increasingly important and complex area of corporate communications. Forward, Preface, Towards an Understanding of Corporate Communications, Audiences - Who - and Where - are the Key Publics, Corporate Identity - the Role and Value of Corporate Identity Programs, Strategy, Using the Tools Provided by Corporate Communications, Crisis Communications - Truth at All Costs, The Background of the Communication Executive, A Bright Future for Corporate Communication, References, Index.